History of the Basel Institute for Immunology - Lefkovits, Ivan (Karger, 2017)
ectures, Parties, and Nobel Prizes: living and researching at the Basel Institute for Immunology By the early seventies of the 20th century, the Basel Institute for Immunology had become one of the largest - and certainly the most prominent - immunology institutes in the world. Its lean structure was highly successful, and the quality of the research and its reputation remained outstandingly high throughout the three decades it existed. This book describes the institute's history from its conception and the laying of the foundation stone in 1969 by the pharmaceutical company Roche to the triumph of three Nobel Prizes (1984 and 1987) for Niels K. Jerne, Georges Köhler and Susumu Tonegawa. Can all this be portrayed to make the layman understand it and the scientist relish it? Indeed, the book succeeds in tuning in to what fascinates students, advanced researchers and scientists, historians, policy makers and philanthropists alike. The narrative reveals many aspects of the institute's life and also describes all its research and achievements. Immunologists at every level, from beginners to old hands, will find something of interest to them in this history, and some readers will even make use of the huge database (documents, pictures and films) linked to the book by hundreds of QR codes.